In vitro evaluation of potential drug interactions mediated by cytochrome P450 and transporters for luseogliflozin, an SGLT2 inhibitor. (3rd April 2017) - Chino, Yukihiro; Hasegawa, Masatoshi; Fukasawa, Yoshiki; Mano, Yoko; Bando, Kagumi; Miyata, Atsunori; Nakai, Yasuhiro; Endo, Hiromi; Yamaguchi, Jun-ichi
Abstract: 1. We evaluated potential in vitro drug interactions of luseogliflozin, a sodium-glucose cotransporter 2 (SGLT2) inhibitor, mediated by CYP inhibition, CYP induction and drug transporters using human liver microsomes, primary hepatocytes and recombinant cells-expressing efflux or uptake transporters, respectively. 2. Human CYP inhibition studies indicated that luseogliflozin was a weak inhibitor for CYP2C19 with an IC50 value of 58.3 μM, whereas it was not an inhibitor of the other eight major isoforms that were tested. The exposure of primary hepatocytes to luseogliflozin for 72 hrs weakly induced CYP3A4 at a concentration of 10 μM, whereas it did not induce CYP1A2 or CYP2B6 at concentrations of 0.1–10 μM. 3. An in vitro transport study suggested that luseogliflozin is a substrate for human P-glycoprotein (P-gp), but not for breast cancer resistance protein (BCRP), organic anion transporting polypeptide (OATP) 1B1 and OATP1B3, organic anion transporter (OAT) 1 and OAT3, or organic cation transporter (OCT) 2. Luseogliflozin weakly inhibited OATP1B3 with an IC50 value of 93.1 μM, but those for other transporters are greater than 100 μM. 4. Based on the therapeutic plasma concentration of the drug, clinically relevant drug interactions are unlikely to occur between luseogliflozin and coadministered drugs mediated by CYPs and/or transporters.